Sparsam aber teuer. - Forum Stadtpark Graz (Graz : Forum Stadtpark Graz, 1987)
Anüll, Ian ; Archetti, Luigi ; Herzog, Christoph ; Liechti, Peter ; Signer, Roman ; Schiess, Adrian ; Zäch, René
Sparsam aber teuer, Forum Stadtpark Graz, Mai - Juni 1987
boek